Class size, class ranking and students' achievement - Yahaya, Nadzira; Kadri, Mohd. Halim; Ahmad Yahya, Naimah (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2003)
This study investigates the effect of class size and class ranking on the achievement of accounting students. T test and regression analyses were used to analyze the data. The results of the t-test on class size indicated that students in small classes performed better than students in large classes in the on going assessment whereas students in large classes performed better than students in small classes in the final exam. The T test on class ranking indicated that 'ranking 1' class students had consistently outperformed their counterparts in 'ranking 2' classes in the on-going assessment, final exam and overall achievement. Regression analysis indicated that class size, class ranking and on-going assessment contributed significantly to the prediction of students' overall achievement.